Сервіси та додатки для впровадження AR у видавничо-поліграфічну галузь - Романенко, А. С.; Шипова, М. К. (ХНУРЕ, 2025)
Augmented Reality (AR) is transforming the publishing and printing industries by integrating digital elements like videos and 3D models into printed materials. Key AR tools include Vuforia, Spark AR, and 8th Wall for mobile and web-based applications, while ARKit, ARCore, and Unity enable advanced AR development. Cloud platforms like UniteAR simplify AR adoption, enhancing digital color management and automation in printing. WebAR solutions, such as A-Frame, provide accessible AR experiences. AR implementation boosts audience engagement and drives digital innovation in publishing.
Keywords: видавничо-поліграфічна галузь; впровадження AR